#### Answer

$x=5$ and $x=1$

#### Work Step by Step

The given equation is
$\Rightarrow x^2-6x+5=0$
Standard equation.
$\Rightarrow ax^2+bx+c=0$
We have $a=1,b=-6$ and $c=5$
Quadratic formula.
$\Rightarrow x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}$
Substitute all the values into the formula.
$\Rightarrow x=\frac{-(-6)\pm\sqrt{(-6)^2-4(1)(5)}}{2(1)}$
Clear the parentheses.
$\Rightarrow x=\frac{6\pm\sqrt{36-20}}{2}$
Simplify.
$\Rightarrow x=\frac{6\pm\sqrt{16}}{2}$
Evaluate the square root.
$\Rightarrow x=\frac{6\pm4}{2}$
The solutions are.
$\Rightarrow x=\frac{6+4}{2}$ and $x=\frac{6-4}{2}$
Simplify.
$\Rightarrow x=5$ and $x=1$.